Analisis Performa Metode Perceptual Color Transfer Dalam Peningkatan Kualitas Citra - Ina, Osmanila Tamo; Himamunanto, AR; Budiati, Haeni (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The eye, as the sense of human vision, not only serves to see objects but also builds perceptions of the objects seen so that, in this case, it can judge images from different perspectives. Improved image quality is required because images often experience decreased quality caused by many factors, including being too dark, blurred, less sharp, too bright, and other factors. Perceptual Color Transfer is one of the most popular methods used in research. This method changes the color of an image to match the characteristics of another image, while maintaining the visual quality and naturality of the image. By considering the way humans perceive color, this method produces visual and consistent color adjustments that can contribute to improving the overall image quality. The color spaces used in this study are the lαβ and HSV color spaces using the MSE (Mean Square Error) and PSNR (Peak Signal to Noise Ratio) parameters. The results of the study show that the Perceptual Color Transfer method can be a good alternative to image processing techniques in light and dim light conditions, with the best average MSE and PSNR results in dark source image color transfer in the HSV color space of 0.0678021 and 21.43221, as well as the best mean results in light source image color transfer in Lαβ spaces of 0.0608865 and 20.03709.